Contribution of flagella and motility to gut colonisation and pathogenicity of Salmonella Enteritidis in the chicken - Barbosa, Fernanda de Oliveira [UNESP]; Freitas Neto, Oliveiro Caetano de; Alves Batista, Diego Felipe [UNESP]; Almeida, Adriana Maria de [UNESP]; Rubio, Marcela da Silva [UNESP]; Rodrigues Alves, Lucas Bocchini [UNESP]; Vasconcelos, Rosemeire de Oliveira [UNESP]; Barrow, Paul Andrew; Berchieri Junior, Angelo [UNESP] (Soc Brasileira Microbiologia, 2017)
Salmonella Enteritidis causes fowl paratyphoid in poultry and is frequently associated to outbreaks of food-borne diseases in humans. The role of flagella and flagella-mediated motility into host-pathogen interplay is not fully understood and requires further investigation. In this study, one-day-old chickens were challenged orally with a wild-type strain Salmonella Enteritidis, a non-motile but fully flagellated (SE Delta motB) or non-flagellated (SE Delta fliC) strain to evaluate their ability to colonise the intestine and spread systemically and also of eliciting gross and histopathological changes. SE Delta motB and SE Delta fliC were recovered in significantly lower numbers from caecal contents in comparison with Salmonella Enteritidis at early stages of infection (3 and 5 dpi). The SE Delta motB strain, which synthesises paralysed flagella, showed poorer intestinal colonisation ability than the non-flagellated SE Delta fliC. Histopathological analyses demonstrated that the flagellated strains induced more intense lymphoid reactivity in liver, ileum and caeca. Thus, in the present study the flagellar structure and motility seemed to play a role in the early stages of the intestinal colonisation by Salmonella Enteritidis in the chicken. (C) 2017 Sociedade Brasileira de Microbiologia. Published by Elsevier Editora Ltda.
Keywords: Mutation; Flagellum; Virulence factors; Poultry; Gut colonisation